The patterns of breast-feeding and their effect on the time of resumption of menses (Faculty of Medicine Universitas Indonesia, 2002)
The percentage of mother who had full/exclusive breast-feeding for four months after birth are 50%, and only less than 15% continued full/exclusive breast-feeding for up to the first six months afier birth. The mean duration of full/exclusive breast-feeding is 3.3 months. The median time of the resumption of menses in this study is 186 days (CI: 177-195 days). The median time of resumption of menses significantly associated with both the mean duration of full/exclusive breast-feeding and the average suckling frequency. The longer the mean duration of full/exclusive breast-feeding and the more the average of suckling frequency, the longer the median time of resumption of menses. The median time of resumption of menses in respondent who practiced full/exclusive breast-feeding up to three and more than three months are 149 (CI: 121-177) and 199 (CI: 186-212) days, respectively. And in the mothers who breast fed their infant for up to six times and more than 6 times per day the median time of resumption of menses are 125 (CI: 90-160) and 191 (CI: 181-201) days, respectively. (Med J Indones 2002; 11: 106-19)Keywords : breastfeeding, lactational amenorrhoea, resumption of menses